Pengembangan lembar kegiatan siswa (LKS) berbasis discovery learning pada materi bentuk aljabar untuk siswa kelas VII SMP Miftahul Huda Kabupaten Blitar - Octavita Cahyaningtyas; Santi Irawati (Jurnal MIPA dan Pembelajarannya (JMIPAP), 2021)
The purpose of the development carried out is to produce student activity sheet based on discovery learning on algebra for grade VII students of Miftahul Huda Middle School in Blitar Regency that is valid, practical, and effective. The development model refers to the ADDIE development model which consists of: analysis, design, development, implementation, and evaluation. The results showed that LKS was declared valid with a validity score of 3.43. Student’s activity sheet also fulfills practical criteria based on student response questionnaires with a practicality score of 3.5, based on the observation sheet of teacher activity with a practicality score of 3.8, and based on the observation sheet of student activity with a practicality score of 3.66. The developed student worksheets also fulfills the effective criteria with a percentage of 90 percent of students getting a score above the minimum pass criteria Tujuan penelitian ini yaitu untuk menghasilkan LKS berbasis discovery learning pada materi bentuk aljabar bagi siswa kelas VII SMP Miftahul Huda Kabupaten Blitar yang valid, praktis, dan efektif. Model pengembangan merujuk pada model pengembangan ADDIE yaitu: analisis, desain/perancangan, pengembangan, implementasi, dan evaluasi. Hasil validasi menunjukkan bahwa LKS dinyatakan valid dengan skor kevalidan 3,43. LKS juga memenuhi kriteria praktis berdasarkan angket respon siswa dengan skor kepraktisan 3,5, berdasarkan lembar observasi aktivitas guru dengan skor kepraktisan 3,8, dan berdasarkan lembar observasi aktivitas siswa dengan skor kepraktisan 3,66. LKS yang dikembangkan juga memenuhi kriteria efektif dengan persentase 90 persen siswa mendapat nilai di atas KKM.